Getúlio Vargas biografado: análise de biografias publicadas entre 1939 e 1988 - Marcelo Hornos Steffens (2008)
The main purpose of this work is to analyze the biographical production about the former Brazilian president Getúlio Vargas written between the years 1939 and 1988. In doing so, we have identified the images about Vargas that were built up by the authors of eight selected biographies and investigated the relationships between these biographies, their historiographic discussions and the contextual tensions under which such writings have been published. Furthermore, we aim at tracking both the permanent and changing aspects of the biographical genre, throughout these decades, its similarities with the academic and fictional writings as well as the contacts and interchanges of these two fields of knowledge.